The difference growth and development of army worm (Spodoptera litura) on five host plants - MARIDA SANTI YUDHA IKA BAYU; AYDA KRISNAWATI (Smujo International, 2016)
Abstract. Bayu MSYI, Krisnawati A. 2016. The difference growth and development of armyworm (Spodoptera litura) on five host plants. Nusantara Bioscience 8: 161-168. Spodoptera litura is the important pest on soybean in Indonesia. The objective of this study was to determine the best feed that supports the development of S. litura and can be used for mass rearing of S. litura. This research was conducted in the Laboratory of Entomology, Indonesian Legume and Tuber Crops Research Institute on March-April 2014 using randomized complete design, five treatments, and 30 replicates. The treatments were Glycine max, Jatropha curcas, Ricinus communis, Ipomoea aquatica, and Amaranthus viridis. One leaf of each host plant was entered into test tube and was infested by one larva of S. litura 0 days after emergence. The result showed that feeds significantly affected the body size, survival rate, developmental time, reproduction, and longevity of S. litura. The longest and heaviest larvae were found on I. aquatica, 28.5 mm and 0.42 g respectively. The longest and heaviest pupae were found on I. aquatica, 19.3 mm, and 0.36 g respectively. The faster developmental time was found on I. aquatica (22.2 days) and R. communis (22.4 days). Furthermore, total egg masses produced by female were high on I. aquatica (11.6 egg masses). In conclusion, I. aquatica and R. communis leaves were found to be preferred for S. litura life which shown the best growth and development of this pest, so it can be used as feed for mass rearing of S. litura.